Study of Problems and Feasibility of Coffee Business - Hardita, I Wayan Agung; Arisena, Gede Mekse Korri (JURNAL AGRIBISAINS, 2023)
Coffee is a mainstay of the plantation sector which has long been a driving force for the economy in Indonesia which has export value. The still not optimal production of coffee in Indonesia has a lot to do with productivity. Factors causing the low productivity of Indonesian coffee include lack of mastery of Good Agricultural Practices (GAP) and Good Handling Practices (GHP), low-quality beans at the farm level, attacks by plant-disturbing organisms, old plants that are no longer productive and farmer institutions that are still weak. Seeing the conditions of the existing problems, the development of coffee businesses needs to be studied for the feasibility of the business. The method used in conducting a business feasibility financial analysis is Net Present Value (NPV), Internal Rate of Return (IRR), Net B/C Ratio, Gross B/C Ratio, R/C Ratio , Return Of Investment (ROI), Payback Period and Profitability Index (PI). The method used is literature study by conducting a review of ten journals related to research. All journals use Net Present Value (NPV), Internal Rate of Return (IRR) and Payback Period calculations. Net B/C Ratio is used by eight journals. Profitability Index (PI) is used by two journals. The Gross B/C Ratio is used by the three journals. R/C Ratio and , Return of Investment (ROI) are only used by one journal. The results of this study are expected to be a reference in assessing the feasibility of the coffee business.